2015
DOI: 10.1038/jcbfm.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Metabolic Activity after Resuscitation with Liposome-Encapsulated Hemoglobin in a Rat Model of Hypovolemic Shock

Abstract: We examined the effect of resuscitation with liposome-encapsulated hemoglobin (LEH) on cerebral bioenergetics in a rat model of 45% hypovolemia. The rats were resuscitated with isovolemic LEH or saline after 15 minutes of shock and followed up to 6 hours. Untreated hypovolemic rats received no fluid. The cerebral uptake of F-18-fluorodeoxyglucose (FDG) was measured by PET, and at 6 hours, the brain was collected for various assays. Hypovolemia decreased cellular adenosine triphosphate (ATP), phosphocreatine, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…4), LEH resuscitation reduced the physiological stress, creating a pro-survival phenotype. Although we did not intently looked for survival statistics in this study, the findings described in this work also corroborate our recent reports that the correction of volume and oxygen deficits by LEH recovers the cerebral glucose metabolism, oxygen metabolism, and tissue energetics in hemorrhagic shock (Awasthi et al, 2010; Awasthi et al, 2007; Rao et al, 2015). Notwithstanding the salutary effects of LEH described in this work and despite the report that the use of non-phospholipid anionic lipid reduces the host immune response to liposomes containing anionic phospholipids (Sou and Tsuchida, 2008), the reported constitution of LEH should to be evaluated for its immune response in a repeat injection trial of longer duration.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…4), LEH resuscitation reduced the physiological stress, creating a pro-survival phenotype. Although we did not intently looked for survival statistics in this study, the findings described in this work also corroborate our recent reports that the correction of volume and oxygen deficits by LEH recovers the cerebral glucose metabolism, oxygen metabolism, and tissue energetics in hemorrhagic shock (Awasthi et al, 2010; Awasthi et al, 2007; Rao et al, 2015). Notwithstanding the salutary effects of LEH described in this work and despite the report that the use of non-phospholipid anionic lipid reduces the host immune response to liposomes containing anionic phospholipids (Sou and Tsuchida, 2008), the reported constitution of LEH should to be evaluated for its immune response in a repeat injection trial of longer duration.…”
Section: Discussionsupporting
confidence: 88%
“…Since any investigational product for resuscitation should prevent the multi-organ injuries and systemic inflammatory response syndrome (SIRS) caused by hypoxia and hypoperfusion, the goal of this study was to determine the effect of resuscitation with test LEH on the plasma levels of pro-inflammatory cytokines and indicators of organ injury in a rat model of hemorrhagic shock. Earlier, we have shown that the test LEH preparation was effective in restoring the perturbed cerebral energy metabolism in the same model (Rao et al, 2015). More recently, we reported that this LEH preparation prevents deterioration of proteostatic mechanisms in the gut tissue (Rao et al, 2016).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Correspondingly, the anion gap in EFLEH group was significantly increased as compared to the baseline levels, suggesting the presence of anion gap acidosis. Similar effect was observed when the hemorrhaged rats were infused with LEH alone (Rao et al 2015). Although the precise reason for this phenomenon is unclear, we suspect albumin in our LEH preparation as a possible factor.…”
Section: Resultssupporting
confidence: 66%
“…We also supplemented EF24-treatment with LEH infusion to study whether co-administration of LEH will augment the efficacy of EF24. Recently, we have shown that LEH preparation used in this work protects brain metabolic activity after hemorrhagic shock (Rao et al 2015). The data discussed below indicate that EF24 administration alone considerably improves the bioenergetics of brain, and the additional benefits of LEH infusion were only incremental.…”
Section: Resultsmentioning
confidence: 94%